Самоактуализация – условие развития личности учащегося - Толегенова, Ш.Т. (My University, 2016)
The conditions of self-actualized person, the model of investigated activity, criteria of guilty of educational results.
Keywords: self-actualization; self-realization; person; psychological and pedagogical support.